Femtosecond laser writing of nonlinear waveguides in Gorilla® Glass and L-threonine organic crystals - Almeida, Gustavo Foresto Brito de (2018)
Femtosecond laser inscribed waveguides inside the bulk of materials have shown great relevance for the development of photonic optical circuits. Due to high intensity, long interaction length and strong light confinement, nonlinear optical effects are significant to pulse propagation within the waveguide. Therefore, it is important to search for new and better platforms to host photonic devices, as well as, to analyze its linear and nonlinear optical properties. In this dissertation, we have studied the inscription of nonlinear waveguides in Gorilla Glass (strengthened alkali aluminosilicate glass) and in L-threonine organic crystals. Initially, we studied the nonlinear refractive index of Gorilla Glass, demonstrating that it presents an approximately constant value of n2 = (3.3 ± 0.6) × 10-20 m2/W over the spectral region from 490 nm up to 1.5 µm. Single-mode waveguides written in Gorilla Glass presents propagation losses on the order of (0.35 ± 0.01) dB/mm, which is comparable to other waveguides inscribed in silicate glasses. In the nonlinear regime, the guided pulse presented spectral broadening, compatible with the measured n2 value, and white-light continuum generation. The generation of new frequencies is due to self-phase modulation and stimulated Raman scattering effects, both associated with third-order nonlinearities of Gorilla Glass. In a second part, we inscribed cladding waveguides in L-threonine organic crystal, in order to explore its second-order nonlinearities. After their linear characterization, that revealed propagation losses of (0.5 ± 0.1) dB/mm, we obtained guided second harmonic generation in the ultraviolet region. The written waveguide presented a normalized power conversion efficiency of (10.3 ± 0.4) % (MW cm2)-1 and approximately four times higher normalized intensity conversion efficiency than the crystal itself. Such enhancement effect was attributed to the influence of the waveguide dispersion in the phase-matching condition necessary for second harmonic generation. In general, the results presented here expand the knowledge on femtosecond laser writing of waveguide in organic and inorganic materials, and their nonlinear properties, which are relevant for developing photonic devices.